Evaluation of herbicides for chemical weed control in lily bulb production - Marinangeli, Pablo Alejandro (2010)
Information on chemical weed control in lily bulb production in South America is scarce. Greenhouse and field studies were conducted to evaluate the phytotoxic effect and weed control of herbicides applied PRE and POST in lily bulb production in Argentina. In greenhouse studies, bromoxynil, 415 g ai ha-1; fluroxypyr, 200 g ai ha-1; metsulfuron, 3 g ai ha-1; iodosulfuron-methyl-sodium, 3 g ai ha-1 metsulfuron, 3 g ai ha-1; oxyfluorfen, 240 g ai ha-1; ioxynil, 529 g ai ha-1; and linuron, 750 g ai ha-1, produced severe phytotoxicity or death of bulbs. Glyphosate at 720 g ai ha-1 and aclonifen at 720 g ai ha-1 produced little to no symptoms and were considered safe to apply to lilies. In field conditions, PRE herbicides metolachlor, 960 g ai ha-1 atrazine, 1,500 g ai ha-1, and metolachlor, 960 g ai ha-1 flumetsulam, 80 g ai ha-1, provided good weed control but were phytotoxic for lily plants, with chlorosis as the main symptom. Metolachlor plus linuron resulted in little or no symptoms of injury and no reduction in bulb yield. Diuron, 800 g ai ha-1 POST was the most effective treatment without phytotoxicity, and, in combination with metolachlor, 960 g ai ha-1 linuron, 750 g ai ha-1 PRE, controlled weeds until 40 d after diuron application without yield reduction. Results obtained with glyphosate indicate that the Lilium genus presents some tolerance to this herbicide, which justifies further evaluation for weed control in lily bulb production.